Comparative Analysis of Income of KTH Pattiro and KTH Lanniti on Trigona sp Honeybee Product in Rompegading Village, Cenrana District, in District Maros - Andi Nur Imran; Andi Khairil A.Samsu (Universitas Andi Djemma Palopo, 2023)
The aim of the study was to find out how much the comparison and difference in income of KTH Pattiro and KTH Lanniti in the production of honey bee forest products Trigona sp in Rompegading Village, Cenrana District, Maros Regency. The data collection method was carried out through interviews with members of the Forest Farmer Group using a questionnaire. Respondents were determined by census as many as 30 people consisting of 15 members of the Pattiro Forest Farmers Group and 15 members of the Laniti Forest Farmers Group. The results showed that the comparison or comparative income of the Pattiro forest farmer group was Rp. 17,205,000/year, with an average forest farmer group income of Rp. 1,147,000/year. Meanwhile, the Lanniti forest farmer group's income from Trigona sp madi bees is Rp. 19,241,000/year, with an average income of Rp. 1,1281,733/year with a difference in income of Rp. 2,036,000/year. Compared to the district minimum wage (UMK) of Maros district, which is around 2,135,000/month, the contribution of Trigona sp honey bees is around 5% per person per month or its contribution to income is still in the very small category.